The Influence of the Flypaper Effect and Fiscal Stress on Provincial Financial Performance in Sulampua Island with Tax Effort as an Intervening Variable - Sudarwinti; Rusydi, Bahrul Ulum (Universitas Islam Negeri Alauddin Makassar, 2024)
This research is expected to serve as a consideration and evaluation material for stakeholders, particularly local governments on Sulampua Island, in formulating various policies, making decisions, and optimizing budgets as efforts to improve regional financial performance. The study employs a quantitative literature review method, sourcing data primarily from journals and various other references accessed through supporting websites on the internet. Data collection was conducted using documentation. The object of observation consists of 80 cross-sectional data points from 10 provinces on Sulampua Island for the period 2016–2023. The test results indicate that the flypaper effect has a negative and significant partial effect on regional financial performance, while fiscal stress has a negative but not significant partial effect. Furthermore, tax effort is found to moderate the relationship between the flypaper effect and regional financial performance, as well as the relationship between fiscal stress and regional financial performance on Sulampua Island.